Log in to add a comment

Log in to add a comment

The Brainliest Answer!

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.

Use the formula, d/dx(u*v) = u* d/dx(v) + v* d/dx(u)

d/dx(x*cosx)

= x* d/dx(cosx) + cosx* d/dx(x)

= x*(-sinx) + cosx * 1

= -x.sinx + cosx

d/dx(x*cosx)

= x* d/dx(cosx) + cosx* d/dx(x)

= x*(-sinx) + cosx * 1

= -x.sinx + cosx

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.

Okay.... !!
Let , y = xcosx ------(1)
Using product rule ,
d/dx[f(x).g(x)] = f(x).d/dx{g(x)} + g(x).d/dx{f(x)}
Differentiating equation 1 w.r.t. 'x'
dy/dx = x(-sinx) + cosx
dy/dx = cosx - xsinx